ChemInform Abstract: Highly Efficient Oxidation of Benzyl Alcohols Using the Catalytic System Sulfoxide/Oxo‐Complexes. Issue 8 (1st March 2013) - Sousa, Sara C. A.; Bernardo, Joana R.; Fernandes, Ana C.
Abstract Conditions A) are elaborated as the most efficient ones: primary alcohol substrates afford good to excellent yields of the corresponding aldehydes, whereas secondary alcohols (V) produce only moderate yields.